2011
DOI: 10.4103/0972-5229.92070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of advanced cardiac life support training program on the outcome of cardiopulmonary resuscitation in a tertiary care hospital

Abstract: Background:Guidelines on performing cardiopulmonary resuscitation (CPR) have been published from time to time, and formal training programs are conducted based on these guidelines. Very few data are available in world literature highlighting the impact of these trainings on CPR outcome.Aim:The aim of our study was to evaluate the impact of the American Heart Association (AHA)-certified basic life support (BLS) and advanced cardiac life support (ACLS) provider course on the outcomes of CPR in our hospital.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 14 publications
(17 reference statements)
0
27
0
2
Order By: Relevance
“…The development of specific, evidence‐based clinical guidelines for human cardiopulmonary resuscitation (CPR), based upon extensive surveys of the literature by the International Liaison Committee on Resuscitation (ILCOR) has allowed consistent training for human healthcare professionals and the lay public, leading directly to improved outcomes . No comparable evidence‐based guidelines have been available in veterinary medicine, although recommendations on practical execution of CPR in small animals have been published .…”
Section: Introductionmentioning
confidence: 99%
“…The development of specific, evidence‐based clinical guidelines for human cardiopulmonary resuscitation (CPR), based upon extensive surveys of the literature by the International Liaison Committee on Resuscitation (ILCOR) has allowed consistent training for human healthcare professionals and the lay public, leading directly to improved outcomes . No comparable evidence‐based guidelines have been available in veterinary medicine, although recommendations on practical execution of CPR in small animals have been published .…”
Section: Introductionmentioning
confidence: 99%
“…[17242526] A third factor that might result in higher survival rates is the level of training of the resuscitation team members and their adherence to resuscitation guidelines. Many previously published studies reported better survival rates after formal resuscitation training,[2728293031] while Curry and Gass[32] found that the death rate was not lower when resuscitation was performed by BLS-trained staff in comparison to untrained staff.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary resuscitation by trained providers in a case of cardiac arrest has been proven to have survival benefit across the world. (1), (2) Many studies have been done regarding predictors of survival outcomes in SCA yet little data exists from India and other parts of the developing world and other parts of the developing world. (3), (4), (5), (6) In this study, we aim to look at the effectiveness of cardiopulmonary resuscitation when performed according to the American Heart Association's Advanced Cardiac Life Support (ACLS) 2010 guidelines.…”
Section: Introductionmentioning
confidence: 99%